Structural effects of unequal leg lengths in lattice steel towers with the D-type bracing system. (December 2021) - Chen, Chun-Chung; Siao, Sheng-Yuan; Jiang, Chi-Rung; Lee, Bo-Han; Yeh, Fang-Yao
Abstract: This paper presents a structural modeling analysis of transmission towers with varied leg length combinations to examine the structural effects of unequal leg lengths. Power transmission towers in mountainous areas often use unequal leg lengths to accommodate the changing slope of the terrain. In this study, three types of 345 kV steel transmission towers with the D-type bracing system were considered as analytical examples to discuss the internal force distribution of the tower structure subjected to a load under a fully wired condition. Different tower structural types exhibit similar structural characteristics. The upper part of the force distribution of a tower structure is less affected by varied leg length configurations. The central parts affected by unequal leg lengths are the extension part and the tower leg component. Analytical results indicate the critical elements of tower structures with unequal leg lengths, which can serve as a valuable reference for disaster prevention and reduction. In this study, the primary elements of the towers were all under the permissible strength even with the leg length differences exceeding the current specifications. This implies that adjusting the regulation of leg length differences of a transmission tower with unequal leg lengths can serve as the basis for future research, highlighting the advantages of unequal leg length tower applications.